Implementation Facilitators and Challenges of a Place-Based Intervention to Reduce Health Disparities in Harlem Through Community Activation and Mobilization - VanDevanter, Nancy; Zhong, Lynna; Dannefer, Rachel; Manyindo, Noel; Walker, Sterling; Otero, Victor; Smith, Kimberly; Keita, Rose; Thorpe, Lorna; Drackett, Elizabeth; Seidl, Lois; Brown-Dudley, La'Shawn; et al. (Frontiers in Public Health, 2022)
Background: To address significant health inequities experienced by residents of public housing in East and Central Harlem compared to other New Yorkers, NYC Department of Health and Mental Health (DOHMH) collaborated with community and academic organizations and the New York City Housing Authority to develop a place-based initiative to address chronic diseases in five housing developments, including a community activation and mobilization component led by community health organizers (CHOs). Purpose: Guided by the Consolidated Framework for Implementation Research (CFIR), we evaluated the initial implementation of the community activation and mobilization component to systematically investigate factors that could influence the successful implementation of the intervention. Methods: Nineteen in-depth qualitative interviews were conducted with a purposive sample of CHOs, community members and leaders, collaborating agencies and DOHMH staff. Interviews were transcribed verbatim, and themes and codes were developed to identify theoretically important concepts of the CFIR and emergent analytic patterns. Results: Findings identified important facilitators to implementation: positive community perception of the program, CHO engagement and responsiveness to community needs, CHO norms and values and adaptability of DOHMH and CHOs to community needs. Challenges included the instability of the program in the first year limited ability to address housing related issues, concerns about long term funding, competing community priorities, low expectations by the community of the program, time and labor intensity to build trust within the community, and the dual roles of CHOs as community advocates and DOHMH employees. Conclusions: Findings will guide future community activation and mobilization activities. The study demonstrates the value of integrating implementation science and health equity frameworks.